Performance Of Accounting Teachers And Education Staff: The Role Of Cyberloafing And Work Stress - Nazaruddin Malik (Jurnal Akademi Akuntansi, 2023)
This study aims to examine the effect of cyberloafing and work stress on the performance of accounting teachers and education staff. This type of research uses a quantitative approach. The number of samples used was 38 respondents. Sources of data in this study were obtained from distributing questionnaires (primary data). The collected data were analyzed using path analysis. The results of this study are that cyberloafing has a significant negative effect on the performance of accounting teachers and education staff. Work stress has a significant negative effect on the performance of accounting teachers and education staff. Work stress does not mediate the effect of cyberloafing on the performance of accounting teachers and education staff. This research has an impact on policies on human resources, especially accounting makers in completing their tasks.